2021
DOI: 10.1089/hum.2020.290
|View full text |Cite
|
Sign up to set email alerts
|

pUDK-HGF Gene Therapy to Relieve CLI Rest Pain and Ulcer: A Phase II, Double-Blind, Randomized Placebo-Controlled Trial

Abstract: BackgroundCritical limb ischemia (CLI) has become a global problem. Less invasive therapy is needed. Hepatocyte growth factor (HGF) is one of the most potent angiogenic protein and the plasmid encoding human hepatocyte growth factor (HGF) is considered to be the most promising gene therapy for CLI. MethodsWe conducted a randomised, double-blind, placebo-controlled trial to assess the e cacy and safety of intramuscular injection of plasmid pUDK-HGF expressing HGF. Pain-at-rest patients and ulcer patients were e… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 21 publications
0
10
0
Order By: Relevance
“…The vector contains complementary DNA of the opioid receptor, which has to be inoculated into the rats’ primary afferent neurons, leading to an upregulation of opioid receptors in the DRG, which may last for up to 6 months [ 144 , 145 ]. Moreover, all these techniques are under preclinical trial, and have not yet been used in humans [ 146 , 147 ].…”
Section: Interventional Methods As An Effective Treatment Approach Ag...mentioning
confidence: 99%
“…The vector contains complementary DNA of the opioid receptor, which has to be inoculated into the rats’ primary afferent neurons, leading to an upregulation of opioid receptors in the DRG, which may last for up to 6 months [ 144 , 145 ]. Moreover, all these techniques are under preclinical trial, and have not yet been used in humans [ 146 , 147 ].…”
Section: Interventional Methods As An Effective Treatment Approach Ag...mentioning
confidence: 99%
“…Twelve randomised controlled trials were identified published since 2017 that tested a range of medical and rehabilitation therapies in patients with CLTI (Table 2). [48][49][50][51][52][53][54][55][56][57][58][59] Women were under-represented, being between 0% and 38% of the enroled patients (Table 2), thus highlighting the unmet need of gender equality in this field. The interventions tested mainly aimed to promote angiogenesis or arteriogenesis using growth factors or stem cells, including plasmids designed to upregulate Hepatocyte growth factor (HGF) or SDF-1, umbilical cord blood platelet gel, bone marrow aspirates, mononuclear cells, mesenchymal stem cells and endothelial cell progenitors.…”
Section: Targets For Treating Limb Ischemia From Findings Of Recent C...mentioning
confidence: 99%
“…59 The other trials had small sample sizes ranging from 20 to 155 and were thus underpowered to test the outcome assessed (Table 2). [48][49][50][51][52][53][54][55][56][57] Accepting this limitation, some promising results were reported for HGF and a number of cell therapies (Table 2). Gu and colleagues tested a HGF plasmid within two cohorts with ischaemic rest pain (n = 119) or ischaemic ulceration (n = 121) at doses ranging between 4 and 8 mg. 48 The proportion of patients with diabetes was not reported.…”
Section: Targets For Treating Limb Ischemia From Findings Of Recent C...mentioning
confidence: 99%
“…Generally, the introduction of genetic material into a host can be achieved by using non-viral vectors, such as plasmid DNA or viral vectors, such as adenovirus and Sendai virus 95 , 96 . Since the first clinical trial for VEGF was conducted in 1996, extensive studies have been performed to assess the effectiveness of other pro-angiogenic factors, such as HGF and FGF ( Table 1 ) 29 , 97 - 101 . Furthermore, many studies using other pro-angiogenic factors, such as angiogenic factor with G-patch and Forkhead-associated domain 1 (AGGF1), human telomerase reverse transcriptase (hTERT), and some microRNAs (miRNAs), also showed promising results in promoting angiogenesis in animal models 102 - 105 .…”
Section: Trends In Therapeutic Angiogenesis For Padmentioning
confidence: 99%
“…In China, another clinical trial for CLI was conducted using an intramuscular injection of plasmid encoding human HGF , pUDK-HGF. The results of its phase II trial in 2014 showed complete pain relief or pain reduction in patients with CLI 97 , prompting the recruitment of phase III clinical trial participants (China Clinical Trial Registry, unique identifier: CTR20181274). Several clinical trials involving the combination of human HGF isoforms are also being held.…”
Section: Trends In Therapeutic Angiogenesis For Padmentioning
confidence: 99%